Solvation of ionic liquids based on N-methyl-N-alkyl morpholinium cations in dimethylsulfoxide – volumetric and compressibility studies. (September 2015) - Marcinkowski, Łukasz; Kloskowski, Adam; Czub, Jacek; Namieśnik, Jacek; Warmińska, Dorota
Graphical abstract: Highlights: In DMSO both volumes and compressibilities of ionic liquids were studied. Molecular dynamics simulations were performed for all studied ionic liquids. V Φ of DMSO solutions of [Mor1, R ][TFSI] decrease with increasing IL concentration. Results indicate that [Mor1, R ][TFSI] are structure breakers in dimethylsulfoxide. Obtained results are the consequence of the cation size of the ionic liquid. Abstract: The density and sound velocity of the solutions of ionic liquids based on N -alkyl- N -methyl-morpholinium cations, N -ethyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide, N -butyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide, N -methyl- N -octyl-morpholinium bis(trifluoromethanesulfonyl)imide and N -decyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide in dimethylsulfoxide were measured at T  = (298.15 to 318.15) K and at atmospheric pressure. The apparent molar volume and apparent molar compressibility values were evaluated from density and sound velocity values and fitted to the Masson equation from which the partial molar volume and partial molar isentropic compressibility of the ILs at infinite dilution were also calculated at working temperatures. By using the density values, the limiting apparent molar expansibilities were estimated. The effect of the alkyl chain length of the ILs and experimental temperature on these thermodynamic properties is discussed. In addition, molecular dynamics simulations were used to interpret the measured properties in terms of interactions of ILs with solvent molecules. Both, volumetric measurements results and molecular dynamics simulations for ionic liquids in dimethylsulfoxide were compared and discussed with results obtained for the same IL in acetonitrile.